MG-109 Revisiting a clinical diagnosis 15 years later with the aid of whole exome sequencing: Osteopetrosis versus harderophorphyria. (4th December 2015) - Mendoza, Roberto; Dupuis, Lucie; Kannu, Peter; Hartley, Taila; Bareke, Eric; Boycott, Kym
Abstract : The advent of whole exome sequencing (WES) has revolutionised gene discovery and led to the identification of atypical phenotypes for well-known syndromes. Our case illustrates the phenotypic overlap between very different syndromes, harderoporphyria and infantile osteopetrosis, which was only resolved by WES. We report two siblings, both born with severe hepatosplenomegaly, jaundice, thrombocytopenia and anaemia. The eldest child had increased bone density on radiographs and was diagnosed with infantile osteopetrosis. Both children responded well to bone marrow transplant (BMT). Molecular testing was negative for genes involved in infantile osteopetrosis: CLCN7, TCIRG1, OSTM1, TNFSF11A and PLEKHMI1 . Many years later, the family was offered whole exome sequencing to clarify the underlying molecular aetiology. The siblings were found to harbour a homozygous mutation (p. K404E) in the CPOX gene confirming a diagnosis harderoporphyria. No mutations were found in any known genes causing infantile osteopetrosis. Defects of heme biosynthesis enzymes result in porphyrias. Harderoporphyria is caused by homozygous mutations in the CPOX gene which encodes coproporphyrinogen oxidase. Individuals with harderoporphyria exhibit neonatal hyperbilirubinemia, hemolytic anaemia, hepatosplenomegaly and photosensitivity. Infantile osteopetrosis presents with increased bone density, reduction of bone marrow spaces leading to anaemia, hepatosplenomegaly, cranial nerves compression and severe growth failure. It is a lethal condition, but responds well to BMT. Given that both children had undergone BMT, their own hematopoietic precursors would have been replaced by those of the donor. Thus, they would not be expected to manifest a harderoporphyria phenotype. To our knowledge, there have been no reports of increased bone mineral density in patients with harderoporphyria. An initial clinical presentation suggesting a diagnosis infantile osteopetrosis was only challenged after the WES data returned. Since the siblings received BMT in the first year of life, it remains unknown whether increased bone density was a persistent finding. This case report illustrates the clinical utility of WES and the importance of establishing a definitive molecular diagnosis for appropriate genetic counselling and medical management.